2019
DOI: 10.1371/journal.pone.0212443
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between nectin-1 and the human natural killer cell receptor CD96

Abstract: Regulation of Natural Killer (NK) cell activity is achieved by the integration of both activating and inhibitory signals acquired at the immunological synapse with potential target cells. NK cells express paired receptors from the immunoglobulin family which share common ligands from the nectin family of adhesion molecules. The activating receptor CD226 (DNAM-1) binds to nectin-2 and CD155, which are also recognized by the inhibitory receptor TIGIT. The third receptor in this family is CD96, which is less well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…In addition to CD112 and CD155, other Nectins have been recently identified as ligands for TACTILE and TIGIT. Thus, CD111 (Nectin-1 or PVRL1) that was previously described as a receptor for herpes viruses [48] is also a ligand for TACTILE [49], and CD113 (Nectin-3 or PVRL3), that originally was described as a member of Ig-like cell adhesion molecules [50], has recently been identified as a ligand for TIGIT [51].…”
Section: Nectin and Nectin-like Protein: Expression On Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to CD112 and CD155, other Nectins have been recently identified as ligands for TACTILE and TIGIT. Thus, CD111 (Nectin-1 or PVRL1) that was previously described as a receptor for herpes viruses [48] is also a ligand for TACTILE [49], and CD113 (Nectin-3 or PVRL3), that originally was described as a member of Ig-like cell adhesion molecules [50], has recently been identified as a ligand for TIGIT [51].…”
Section: Nectin and Nectin-like Protein: Expression On Tumor Cellsmentioning
confidence: 99%
“…TACTILE is constitutively expressed on resting human and murine NK cells and mediates NK cell-target cell adhesion by interacting with CD155 [40]. In addition, it has been shown that TACTILE also binds to CD111 [23,49,85] (Figure 1).…”
Section: Paired Receptors For Nectin and Nectin-like Proteinsmentioning
confidence: 99%
“…DNAM-1 interacts with both PVR and PVRL2 to counter inhibition, yet does so with lower affinity than either TIGIT or PVRIG. TACTILE preferentially interacts with PVRL1 over PVR (Holmes et al, 2019). The affinity of KIR2DL5 for PVR binding is currently unknown, as is whether any other nectin or nectin-like ligand or receptor can serve as its binding partner.…”
Section: Differential Tigit Expression On Immune Cellsmentioning
confidence: 99%
“…As opposed to DNAM-1, CD96 and TIGIT are inhibitory receptors that, by competing with DNAM-1 for binding to the same ligands, counteract NK cell activation [50]. In particular, CD96 binds PVR [51,52] while TIGIT binds both Nectin-2 and PVR [53,54] (Figure 1). Of note, several nectins are used as entry receptors by different human and animal viruses, thus the expression of both CD96 and TIGIT and their ability to compete with DNAM-1 for the engagement of such ligands are crucial in determining the fate of NK cells in mediating the anti-viral response [55].…”
Section: Dnam-1 Signaling Pathwaymentioning
confidence: 99%